Anal incontinence in patients with fistula-in-ano: a comparative study between LIFT (ligation of inter-sphincteric fistulous tract) and fistulectomy - Vidyanendh, Vijayalakshmi; Karunakaran, Amilthan; Damodharan, Arun; Karuppiah, Venkatesh Balaiah; Madhesan, Vaitheeswaran (International Surgery Journal, 2018)
Background: General surgeons perform surgeries for Fistula in ano day in and day out as elective procedures. Fistula in ano is more common nowadays because of improper hygiene. 3 major basic aims of Fistula in ano surgeries are control of sepsis closure of fistula and maintenance of continence. Post operatively some patients developed anal incontinence due to sphincter injury which affects patients’ day to day activity. The present study compared the utility and effectiveness of two standard procedures LIFT (Ligation of Intersphincteric Fistula Tract) and Fistulectomy in terms of anal incontinence. Methods: This study included 100 patients with fistula in ano during the 6 months period from January 2017 to June 2017. Randomized controlled trial was done to divide the patients into two groups. Group A underwent fistulectomy and Group B underwent LIFT (Ligaton of intersphincteric fistulous tract). Post-operative anal incontinence between the two groups were observed for 6 months. Results: In our study it was observed that four patients of group A (fistulectomy) had anal incontinence whereas no patients in group B (LIFT) developed anal incontinence. Conclusions: LIFT (Ligation of intersphincteric fistulous tract) is a better procedure when compared to fistulectomy in preserving sphincter function and preventing anal incontinence offering better quality of life.